2017
DOI: 10.4238/gmr16029683
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity of Jatropha curcas assessed by ISSR

Abstract: ABSTRACT. Jatropha curcas L. is a highly promising oilseed for sustainable production of biofuels and bio-kerosene due to its high oil content and excellent quality. However, it is a perennial and incipiently domesticated species with none stable cultivar created until now despite genetic breeding programs in progress in several countries. Knowledge of the genetic structure and diversity of the species is a necessary step for breeding programs. The molecular marker can be used as a tool for speed up the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
4
0
3
Order By: Relevance
“…The maximum number of amplified product (8) was observed in the profiles of the primer UBC 827 and primer UBC 836. The minimum number of amplified product (5) was observed in the profiles of primer UBC 841. In the seven accessions, a total of 122 bands were obtained.…”
Section: Issr Molecular Marker Diversitymentioning
confidence: 96%
See 1 more Smart Citation
“…The maximum number of amplified product (8) was observed in the profiles of the primer UBC 827 and primer UBC 836. The minimum number of amplified product (5) was observed in the profiles of primer UBC 841. In the seven accessions, a total of 122 bands were obtained.…”
Section: Issr Molecular Marker Diversitymentioning
confidence: 96%
“…Intensive human intervention for the domestication of the plant is necessary to make the crop profitable [4]. Therefore, the establishment of crops that meet the needs of stable and commercial cultivars with high oil content and tolerance to pests and diseases requires developing a genetic improvement program [5]. However, lack of information exists on molecular characterization of this plant, which makes the determination of genetic variability essential for this program.…”
Section: Introductionmentioning
confidence: 99%
“…Para o cálculo das distâncias genéticas entre cultivares ou acessos, diferentes metodologias são encontradas na literatura, tais como: Jaccard; Russel e Rao; Ochiai; Sokal e Sneath; entre outras (CRUZ, 2008). Para o pinhão-manso, a maior parte dos trabalhos utiliza apenas um ou poucos coeficientes, sendo os mais comuns os de Jaccard, Nei e Li e Coincidência Simples (DÍAZ et al, 2017;RIBEIRO et al, 2017;ALKIMIM et al, 2013;OLIVEIRA et al, 2013;SANTOS et al, 2010).…”
Section: Introductionunclassified
“…The establishment, characterization and suitable use of a germplasm bank representing the genetic variability of the species (core collection) are essential for the success of a breeding program (Díaz et al, 2017). Genetic diversity studies using morphological (Montes Osorio et al, 2014;Pazeto et al, 2015) or/and molecular markers (Basha and Sujatha, 2007;Tanya et al, 2011;Sudheer et al, 2011;Pecina-Quintero et al, 2014) have reported narrow diversity in J. curcas germplasm with exception of some studied Mexican accessions (probable center of origin of physic nut) (Santos et al, 2016;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generation of cultivars with higher productivity, increased oil content and quality, production uniformity, and resistance to biotic and abiotic stresses has been achieved by interspecific breeding (Sujatha, 2013). Congener species exhibit large genetic diversity, with several interesting agronomic traits (Popluechai et al, 2009;de Argollo Marques et al, 2013;Díaz et al, 2017). The closely related evergreen shrub J. integerrima (Sudheer Pamidiamarri et al, 2008) (2n = 2x = 22, Marinho et al, 2018, for instance, carries traits not found in J. curcas, such as setting profuse flowers with uniform blooming on the same inflorescence, presence of woody stem and branches, besides dwarf varieties (Laosatit et al, 2014.…”
Section: Introductionmentioning
confidence: 99%